La cuarta exclusión. Notas sobre lingüística formal - Montalbetti, Mario (2015)
Formal linguistics is posible only if a program of three exclusions is put into place: exclusion of reference, diachrony and the Subject. The first one to embrace this program was Saussure and then, the different versions of structuralism followed suite. However, I would like to suggest here that a fourth exclusion is needed in order to understand theories that emerge in the outer limits of structuralism (Lacan/Milner’s hyper-structuralism), Chomsky’s biologizing proyect and Q. Meillassoux’s absolutizing attempts: the exclusion of meaning.